Efficacy and safety of jaktinib hydrochloride tablets in active axial spondyloarthritis: a multicentre, randomised, double-blind, placebo-controlled phase II clinical trial - Xiaomei Li; Xiaoxia Wang; Jian Wu; Xiao Zhang; Chunde Bao; Shengqian Xu; Lingyun Sun; Juan Wang; Guixiu Shi; Xiaofei Wang; Qing Dai; Antao Xu; et al. (RMD Open)
Objective The objective of this study is to evaluate the efficacy and safety of jaktinib hydrochloride tablets (jaktinib), a Janus kinase inhibitor, in patients with active radiographic axial spondyloarthritis (r-axSpA).Methods Adults with active r-axSpA who met modified New York criteria and had an inadequate response to non-steroidal anti-inflammatory drugs were randomised 1:1:1 to receive jaktinib 75 mg two times per day, 100 mg two times per day, or placebo. The primary and key secondary endpoints were Assessment of SpondyloArthritis international Society 20 (ASAS 20) and ASAS 40 responses, respectively, at week 16. Safety was evaluated by analysing adverse events.Results A total of 107 patients with active r-axSpA were randomised (jaktinib 75 mg two times per day, n=35; jaktinib 100 mg two times per day, n=36; placebo, n=36). In the ASAS20 response rates, the 100 mg two times per day group had the highest response at 61.1%, followed by the 75 mg two times per day group at 57.1%, and the placebo group had the lowest at 33.3% for the 16 weeks of treatment. The ASAS40 response rates were significantly higher with jaktinib (100 mg two times per day group: 47.2%, 75 mg two times per day group: 37.1%) compared with placebo (13.9%). The incidence of treatment-emergent adverse events in the 75 mg two times per day, 100 mg two times per day and placebo groups was 88.6% versus 94.4% versus 86.1%, respectively, with no statistically significant difference among the three groups. No major adverse cardiovascular events, malignancy, thromboembolism or deaths were reported.Conclusions Jaktinib showed good efficacy and tolerability in the treatment of active r-axSpA, with the 100 mg two times per day showing a trend towards better efficacy.Trial registration number NCT04507659.